ANALISIS PENGARUH PENGUNGKAPAN, TRANSAKSI DAN SALDO PIHAK BERELASI TERHADAP HARGA SAHAM SEKTOR KEUANGAN DI BEI - Dwi Septilestari; Bunga Maharani; Aisa Tri Agustini (Universitas Jember, 2018)
Statement of Financial Accounting Standards No. 7 describes the disclosure related party which is considered by the investor for being able to show how much the transaction is and which side the company has a related relationship. The purpose of this study is to examine the effect of disclosure, transactions and balances of related parties to the increase of stock price. The data in this research used secondary data obtained from the official website of the Indonesia Stock Exchange listed in 2014-2016 and included in the financial sector companies. The sampling technique used purposive sampling method. The method used in this research through multiple linear regression analysis method, by doing classical assumption test and hypothesis testing so that later get the result of research conclusion. This study performs simultaneous testing between independent variables to the dependent variable. The result of the research shows that: (1) The disclosure of related parties is not proven able to raise the stock price of financial sector companies in 2014-2016 period, (2) Disclosure of related party transactions and balances is not proven able to raise the stock price of financial sector companies in 2014-2016 period. Keywords: Stock Price, Related Party Disclosure, Transaction Disclosure and Balance, PSAK 07